2018
DOI: 10.4274/jtsm.92486
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light on Quality of Sleep and Life in Breast Cancer Patients

Abstract: ÖzObjective: In Obesity Hypoventilation syndrome (OHS), pulmonary hypertension (PH) is an important morbidity and mortality reason compared to pure Obstructive Sleep Apnea syndrome (OSAS). However, few studies are available in the literature about this subject. For this reason, we evaluated OHS and pure OSAS cases in our study from the point of right heart-related echocardiographic parameters and PH. Materials and Methods: Obese [body mass index (BMI) >30 kg/m 2 ] cases diagnosed by polysomnography were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…These studies included a total of 451 participants, with 234 in the intervention group and 217 in the control group. Of these, five were conducted in the US ( 24 , 30 , 31 , 39 , 40 ), two in Turkey ( 41 , 42 ), one in Canada ( 43 ), and another one in the Netherlands ( 44 ). The average age of the participants in these studies was 55.32 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included a total of 451 participants, with 234 in the intervention group and 217 in the control group. Of these, five were conducted in the US ( 24 , 30 , 31 , 39 , 40 ), two in Turkey ( 41 , 42 ), one in Canada ( 43 ), and another one in the Netherlands ( 44 ). The average age of the participants in these studies was 55.32 years.…”
Section: Resultsmentioning
confidence: 99%
“…As shown, performance bias was the most common type of bias in these studies. Of the nine studies included in the systematic review, five had issues with blinding with four having definite and one possible risk ( 24 , 30 , 31 , 39 , 41 ). Given the design of these studies, it was likely that the blinding issue was more related to research personnel than the participants.…”
Section: Resultsmentioning
confidence: 99%
“…It was found in previous studies that the BWL source did not produce the same effect on sleep quality in treatment groups and that the BWL on cancer patients receiving palliative care had an effect on sleep quality. In a randomized controlled trial, Özkaraman et al (2018) applied BWL (10,000 lux) for 30 minutes a day for a week to breast cancer patients who reported low sleep quality and found that the patients in the treatment group had decreased sleep quality scores albeit not significantly (Özkaraman et al, 2018). They concluded that, unlike in this study, the BWL did not affect sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…The study sample included patients who were between 18 and 54 years of age, who previously received a minimum of 1 course of adjuvant chemotherapy and would receive at least 3 more courses of treatment, who did not have a psychiatric diagnosis, and who obtained 1 to 10 points on the Piper Fatigue Scale. The study sample was determined using the power analysis, which was carried out based on fatigue and quality-of-life mean scores obtained from previous relevant studies 34,35 . As a result, 70 patients were included in the study, 35 for each group based on α = .05 error, 83.59% test power, and d = 0.899 effect size.…”
Section: Methodsmentioning
confidence: 99%
“…The study sample was determined using the power analysis, which was carried out based on fatigue and quality-of-life mean scores obtained from previous relevant studies. 34,35 As a result, 70 patients were included in the study, 35 for each group based on α = .05 error, 83.59% test power, and d = 0.899 effect size.…”
Section: Population and Samplementioning
confidence: 99%